The complete chloroplast genome of Phyllostachys glauca (Bambusoideae), a dominant bamboo species in limestone mountains endemic to China. Issue 3 (2nd July 2020) - Cao, Binbin; Ge, Tingting; Ding, Shixiong; Guo, Chunce
Abstract: Phyllostachys glauca is a dominant species in limestone mountains endemic to China. Here, we characterized its complete chloroplast genome. It is a circular DNA molecule of 139, 689 bp in length, including a pair of 21, 798 bp inverted repeats (IRs), a 12, 872 bp small single-copy (SSC) region and an 83221 bp large single-copy (LSC) region. The total GC content of P. glauca chloroplast genome was 38.9%, and it encodes a total of 137 functional genes, including 89 protein-coding genes, 40 tRNA genes, and 8 rRNA genes. The phylogenetic analysis shows that P. glauca is highly clustered in the Phyllostachys clade (V), sister to the lineage of P. nigra var. henonis + P. sulphurea .